Maize: storing your produce- Advisory booklet No.2 (1982) - Nigerian Stored Products Research Institute; Nigerian Stored Products Research Institute (Lagos: Nigerian Stored Products Research Institute, 1982)
This booklet provides a practical guide to safe storage of maize at all levels. What is recommended in the booklet is also applicable to sorghum, paddy rice, millet and cowpeas.
lje 23/4/2017
Arch
Keywords: Agriculture; Grain storage; Grain production; Nigeria